Perlindungan Hukum bagi Pemegang Hak Atas Tanah yang Dirugikan dalam Program Konsolidasi Tanah - Mosa, Ansella Rambu; Susilo, Hariyanto (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to describe the procedures for implementing land consolidation programs and analyzing legal protections for land rights holders who were harmed in land consolidation programs. The approach used in the research was sociological juridical, with a type of empirical juridical research. Data sources came from data obtained directly from the public or commonly referred to as primary data and other data obtained from library materials or commonly referred to as secondary data. The procedure of implementation of the land consolidation program was carried out through several stages, namely the selection of location and area of the location, socialization, the creation of agreement letters and declarations of the release of land rights, inventory, and the issuance and delivery of certificates. Legal protection for land rights holders who were harmed in the land consolidation program was guided by Article 18 of the Constitution, which stated that landowners were entitled to appropriate compensation if in the implementation of the land consolidation program found burdensome things even cause losses.